High-performance non-doped near ultraviolet OLEDs with the EQE ∼ 6 % and CIEy ∼ 0.03 from high-lying reverse intersystem crossing - Peng, Ling; Lv, Jichen; Xiao, Shu; Huo, Yumiao; Liu, Yuchao; Ma, Dongge; Ying, Shian; Yan, Shouke (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
•A near ultraviolet material mP2MPC is constructed based on the “coupling hardness with softness” design strategy.•The non-doped near ultraviolet organic light-emitting diode exhibits the CIE coordinates of (0.163, 0.028).•The forward-viewing EQE is 6.09 %, and keeps as high as 5.56 % at the practical luminance of 1000 cd m−2.•The green and red phosphorescent devices with mP2MPC as host show the EQEs exceeding 21.5%. Developing high-performance organic fluorophors with short-wavelength emission is both significant and challenging subject in the application of organic light-emitting diodes (OLEDs). In this work, we proposes a “coupling hardness with distortion” design concept to construct an efficient near ultraviolet (NUV) fluorophor mP2MPC with 1,4-dimethyl-2,5-diphenylbenzene as a rotatable bridge via the meta-positons linking rigid and bulky phenanthroimidazole and carbazole groups. As a result, the non-doped OLED with it as emitter not only exhibits an emission peak at 395 nm with the Commission Internationale de l’éclairage coordinates of (0.163, 0.028), but also realizes a high forward-viewing external quantum efficiency of 6.09 % due to the high-lying reverse intersystem crossing. The value still keeps as high as 5.56 % at 1000 cd m−2, showing a small efficiency roll-off. This is one of the highest efficiencies among the non-doped devices with the electroluminescence peak below 400 nm. Moreover, the green and red phosphorescent OLEDs with mP2MPC as host can also show excellent electroluminescence performance with the forward-viewing external quantum efficiencies over 21.5 %, illustrating that mP2MPC should be a prospective material for OLEDs.